Isolation and Identification of Phosphate Solubilizing and Nitrogen Fixing Bacteria from Soil in Wamena Biological Garden, Jayawijaya, Papua - SULIASIH SULIASIH; SRI WIDAWATI (Society for Indonesian Biodiversity, 2005)
A study was undertaken to investigate the occurrence of phosphate solubilizing bacteria (PSB) and nitrogen-fixing bacteria (NFB) from soil samples of Wamena Biological Garden (WbiG). Eleven soil samples were collected randomly to estimate microbial population which used plate count method. The result showed that the microbial population ranged from 5.0x103-7.5x106 cells of bacteria/gram of soil and 5.0x103-1.5x107 cells of bacteria/gram of soil for PSB and NFB respectively. There were 17 isolates which have been identified till genus and species. The isolated microorganism were identified as PSB i.e. Bacillus sp., B. pantothenticus, B. megatherium, Flavobacterium sp., F. breve, Klebsiella sp., K. aerogenes, Chromobacterium lividum, Enterobacter alvei, E. agglomerans, Pseudomonas sp., Proteus sp. and as NFB i.e. Azotobacter sp., A. chroococcum, A. paspalii, Rhizobium sp., and Azospirillum sp.Â© 2005 Jurusan Biologi FMIPA UNS SurakartaKey words: phosphate- solubilizing bacteria, Nitrogen-fixing bacteria, Wamena Biological Garden